A trait‐based approach to marine island biogeography - Débora S. Ferrari; Sergio R. Floeter; Fabien Leprieur; Juan P. Quimbayo (Journal of Biogeography, 2023)
Aim The Island Biogeography Theory (IBT) and its multiple extensions explain species diversity patterns in insular systems. However, how these theories can predict the functional diversity patterns in island systems remains challenging. Here, we evaluated the predictions of the IBT, the General Dynamic Theory of Oceanic Island Biogeography (GDM) and the Glacial‐sensitive model of Island Biogeography (GSM) considering the functional diversity of reef fishes on islands. Location Tropical oceanic islands. Taxon Actinopterygii. Method We combined literature data and online repositories to gather occurrence data and traits of reef fish species for 72 tropical oceanic islands. We then calculated five functional diversity indices (functional richness ‘FRic’, functional evenness ‘FEve’, functional divergence ‘FDiv’, functional over‐redundancy ‘FOR’ and functional vulnerability ‘FVul’). We used generalized additive mixed models to explore relationships among species richness and functional indices. Furthermore, we built Bayesian models to evaluate relationships between the functional diversity indices and several island features (isolation from the nearest reef, past and present reef area, and geological age) and two metrics that reflect the potential influence of Quaternary climatic changes (isolation from Quaternary refugia) and historical contingency (isolation from biodiversity centres). Results We observed higher levels of FRic, FDiv and FOR on the Indo‐Pacific islands, whereas FEve and FVul showed higher values on the Atlantic and Eastern Pacific islands. We identified positive relationships between FRic, FDiv and FOR with species richness but negative relationships with FEve and FVul. We found that past and present reef areas best explained the variation in functional diversity among islands. Main Conclusions The functional diversity of reef fishes on oceanic islands showed a longitudinal gradient, which can be explained by differences in the evolutionary history among marine regions. Furthermore, past and present reef areas were found to be the best predictors of reef fish functional diversity on oceanic islands, extending the IBT, GDM and GSM for marine organisms within a trait‐based framework.